Corrosion resistance of pack aluminized TI-6AL-4V alloy - Casteletti, Luiz Carlos; Takeya, Gustavo Satoru; Rego, Galtiere Correa; Neto, Amadeu Lombardi; Picon, Carlos Alberto [UNESP]; Totten, George Edward (My University, 2015)
Ti 6Al-4V is known as the workhorse of the titanium industry, and this alloy accounts for more than 50% of total titanium usage. It is an alpha+beta alloy that is recommended for use at service temperatures up to approximately 350°C. It offers a combination of high strength, light weight, formability and corrosion resistance which have made it a world standard in aerospace applications. Surface treatments can extend its use range. Aluminizing treatment by powder pack aluminization can produce aluminides with improved characteristics of corrosion and oxidation resistance. In this work, samples of Ti 6Al-4V were aluminized at 1000°C for 2, 4 and 6 hours. The layers obtained were characterized by optical and electron microscopy and potentiodynamic corrosion tests in NaCl solutions (3.5%) and H2SO4. The corrosion tests in NaCl solution showed an improved performance for all treated samples when compared with the untreated substrate. The tests in H2SO4 solution exhibited a lesser improvement, but all the layers produced were similar to or superior in performance relative to the substrate.
Keywords: Pack aluminized; Potentiodynamic corrosion tests; Ti-6Al-4V